(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The contribution aims to examine the main legal challenges related to the use of artificial intelligence in the public sphere. In this context, the problems are peculiar as a consequence of the public nature of the subject involved, of the complex governance and of the significant ethical and social implications. Artificial intelligence solutions in the public sphere must comply with the relevant legislation and may lead to critical issues in the definition of ownership and in the identification of the related responsibilities; compliance with the data protection rules necessary to protect the person can be particularly problematic. The analysis aims to show that the technological approach alone is not enough, but it must be guided by the ability to direct the technique by means of law and by a solid ethical approach, based on accountability, transparency and openness.